2015
DOI: 10.1074/jbc.m115.638700
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation between Two Biosynthetic Enzymes Modifies the Allosteric Regulatory Properties of Both

Abstract: Background: Two enzymes from Mycobacterium tuberculosis involved in aromatic amino acid biosynthesis form a heterooctameric complex. Results: Complex formation boosts the catalytic activity of both enzymes and greatly extends the allosteric effector sensitivity. Conclusion: Enzyme interactions allow complex allosteric machinery of one of the complex partners to be shared. Significance: Sophisticated allosteric responses are delivered through protein-protein interactions, allowing enhanced metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 34 publications
3
53
3
Order By: Relevance
“…Sedimentation velocity experiments were carried out at three protein concentrations under the conditions previously described for the wild type enzyme [21]. At the lowest analyzed concentration, 0.09 mg/mL, a major species with a sedimentation coefficient of 4.0 S can be observed (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Sedimentation velocity experiments were carried out at three protein concentrations under the conditions previously described for the wild type enzyme [21]. At the lowest analyzed concentration, 0.09 mg/mL, a major species with a sedimentation coefficient of 4.0 S can be observed (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, MtuDAH7PS G190P retained the ability to activate MtuCM, demonstrating that the inter-enzyme interaction was intact ( Table 1). [16][17][18] Both the wildtype enzyme and substituted MtuDAH7PS enhanced the activity of MtuCM over 100-fold in similar ways, by lowering the KM value for chorismate and enhancing turnover.…”
Section: Sequence Analysis and Protein Sectors In Type II Dah7psmentioning
confidence: 93%
“…It has been shown that the allosteric machinery of MtuDAH7PS can be utilized by another small protein partner, chorismate mutase (MtuCM), by forming a noncovalent complex. [16][17][18] CM catalyzes a downstream reaction in the shikimate pathway, converting chorismate to prephenate, and is at the start of the branchpoint of the shikimate pathway that leads to the production of Phe and Tyr. It has been shown that complex formation between MtuDAH7PS and MtuCM significantly enhances the catalytic activity of MtuCM.…”
mentioning
confidence: 99%
See 2 more Smart Citations